2022
DOI: 10.19053/20278306.v12.n2.2022.15271
|View full text |Cite
|
Sign up to set email alerts
|

Modelado de tópicos aplicado al análisis del papel del aprendizaje automático en revisiones sistemáticas

Abstract: El objetivo de la investigación fue analizar el papel del aprendizaje automático de datos en las revisiones sistemáticas de literatura. Se aplicó la técnica de Procesamiento de Lenguaje Natural denominada modelado de tópicos, a un conjunto de títulos y resúmenes recopilados de la base de datos Scopus. Especificamente se utilizó la técnica de Asignación Latente de Dirichlet (LDA), a partir de la cual se lograron descubrir y comprender las temáticas subyacentes en la colección de documentos. Los resultados mostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…It is this system that provides the individual with a series of reference mechanisms on which to regulate the process of perception and evaluation of one’s behaviour in such a way that how the results obtained from daily actions are interpreted functions as an input and can modify performance at a later level [ 54 ]. It is interesting, as Yang et al [ 55 ] found, low self-efficacy is associated with an increased risk of worsening disease in chronic patients because chronic patients tend to increase pain intensity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is this system that provides the individual with a series of reference mechanisms on which to regulate the process of perception and evaluation of one’s behaviour in such a way that how the results obtained from daily actions are interpreted functions as an input and can modify performance at a later level [ 54 ]. It is interesting, as Yang et al [ 55 ] found, low self-efficacy is associated with an increased risk of worsening disease in chronic patients because chronic patients tend to increase pain intensity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, sensitivity or recall represents the proportion of correctly classified positive cases [66]. Equation (2) shows the expression to determine sensitivity [67].…”
Section: Accuracy Tp Tn Tp Tn Fp Fnmentioning
confidence: 99%
“…AUC represents the probability of correctly classifying a randomly chosen positive class rather than a randomly chosen negative one [66]. Equation (3) shows the expression to determine the area under the curve.…”
Section: Recall Tp Tp Fnmentioning
confidence: 99%